Pacific Rim Laser Damage 2015: Optical Materials for High-Power Lasers 2015
DOI: 10.1117/12.2185898
|View full text |Cite
|
Sign up to set email alerts
|

Producing fused silica optics with high UV-damage resistance to nanosecond pulsed lasers

Abstract: The laser induced damage to optics has been an issue of paramount importance in laser research community. The low damage threshold of fused silica surfaces predominantly restricts the development of high power and high energy systems. This paper is aimed at improving the surface damage threshold of fused silica substrates by researching the effect of mechanical and chemical defects on laser damage: cracks/scratches and metallic impurities. The cracks were found to close, at least in part, after thermal process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…The damage resistance of scratches vs etched depth was investigated, and the average results of LIDT at the specific etched depth were obtained as the diamond data in Figure show. Although the damage characteristics of scratches are affected by multiple factors in addition to the size of scratches, the bluntness of cracks, etc., our results suggest that deep etching (~25 μm) benefits the LIDT improvement of brittle scratches in that the scratches are blunted and the lateral cracks are vanished by deep etching that is highly deleterious to damage resistance of fused silica. The average of LIDT for 1, 1.5, and 2 N scratches is increased to ~9.1, 6.9, and 6.4 J/cm 2 , respectively, when the material removal amount is ~25 μm.…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…The damage resistance of scratches vs etched depth was investigated, and the average results of LIDT at the specific etched depth were obtained as the diamond data in Figure show. Although the damage characteristics of scratches are affected by multiple factors in addition to the size of scratches, the bluntness of cracks, etc., our results suggest that deep etching (~25 μm) benefits the LIDT improvement of brittle scratches in that the scratches are blunted and the lateral cracks are vanished by deep etching that is highly deleterious to damage resistance of fused silica. The average of LIDT for 1, 1.5, and 2 N scratches is increased to ~9.1, 6.9, and 6.4 J/cm 2 , respectively, when the material removal amount is ~25 μm.…”
Section: Resultsmentioning
confidence: 73%
“…Surface/subsurface defects like metallic impurities, mechanical fractures (scratches, cracks, etc. ), and organic contaminants are found to be potential laser damage initiators . Among them, scratches can reduce laser‐induced damage threshold (LIDT) of optics for multiple reasons, including the weakening of surface due to existing mechanical fractures, thermal effects triggered by the UV‐absorptive impurities embedded within the cracks, and/or the light filed intensification caused by the scratches/cracks .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, it has been shown that the surface layer modification is dependent on the processing parameters applied. Suratwala et al 4 and Wang et al 17 explained that the cerium depth penetration is consistent with a mechanism which depends on the relative rate of hydrolyze between Ce-OCe and Si-O-Si bonds, where the ratio increases with the interface temperature which increases with polishing removal rate. However, the process parameters cannot totally explain the huge differences in depth and concentration.…”
Section: Introductionmentioning
confidence: 90%
“…On the other hand, soft but brittle properties render KDP susceptible to scratches. Scratches generally have significant impact on damage resistance to lasers, which has been demonstrated on fused silica sample [6][7][8][9]. Thus it is of great importance to carry out investigations into the damage characteristics, in particular, the effect of scratches on laser-induced damage of KDP.…”
Section: Introductionmentioning
confidence: 99%